Object-Oriented Software Construction / Prentice Hall International Series in Computer Series - Meyer Bertrand (Prentice Hall, 1988)
This book provides an in-depth presentation of the methods and techniques of object-oriented design, based on a careful assessment of the underlying software engineering issues. Preface, Syntax Notation, Issues and Principles, Techniques of Object-Oriented Design and Programming, Applying Object-Oriented Techniques in Other Environments, Appendices, Bibliography, Index.